Al-Korani (d.: 893 AH) follows in his interpretation of Ghayat Al-Amani on Al-Zamakhshari in matters of faith, Surat Al-Baqara as a model - Salih , Adel; Karim , Qais (Islamic Sciences Journal, 2023)
The interpretation of the Imam al-Qurani is one of the books of the comprehensive interpretations, the sciences and benefits of which are varied, which we find few in others. Because it is in fact a comparative explanatory study, which is not satisfied with mentioning one of the possibilities, nor by presenting one of the sayings without evidence. Important sayings, he supported them in many of them, and objected to them in some of them, which requires editing, and finding the rightness in that as much as possible, so I made the title of my research: ((Comments AL-Koranee (893 H) in his Explication Ghayatul-Amanee, on Al- Zamakhsharee, In matters of faith, Surat Al-Baqara as a paradigm)).